A framework for semantic annotation of geospatial data for agriculture. (2nd June 2009) - Macario, C.G.N.; Medeiros, C.B.
The Web is a huge repository of geospatial information. Efficient retrieval of this information is a key factor in planning and decision-making in many domains, including agriculture. However, standards for data annotation and exchange enable only syntactic interoperability, while semantic heterogeneity presents challenges. This work describes a framework that tackles interoperability problems via semantic annotations, which are based on multiple ontologies. The framework is being developed within a project to support agricultural planning in Brazil. The paper discusses design and implementation issues using a real case study, provides an overview of annotation mechanisms and identifies requirements for annotating agricultural data.